Analysis of C-Organic, Nitrogen, and C/N Ratio Contents in Oil Palm Plantations Soil Owned by the People of Pulau Binjai Village, Kuantan Mudik District, Kuantan Singingi Regency, Riau Province - Chairil Ezward; Tri Nopsagiarti; A. Haitami; Elfi Indrawanis; Gusti Marlina; Haris Susanto; Infitria; Nikmatul Farisya Imanda (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Land conversion from rubber plantations to oil palm plantations is increasingly common in Indonesia, including in Pulau Binjai Village, Kuantan Mudik District, Kuantan Singingi Regency, Riau Province. Land preparation for oil palm plantations can affect soil fertility, particularly nutrient content. This study aims to evaluate the nutrient content in one-year-old oil palm plantations. The methods used in this study included surveys and laboratory analyses. Soil sampling was conducted at 10 locations using purposive random sampling at a depth of 20 cm, with 5 locations sampled using the grid method and 5 using the disc method. Each sample location consisted of 5 subsamples, which were then composited. The results showed that the soil pH in the grid ranged from 5.96 to 6.48 (acidic category), while in the disc it ranged from 6.2 to 6.88 (acidic to neutral category). The organic carbon content in the grid ranged from 2.61 to 3.74 (medium to high category), and in the plate from 2.82 to 4.28 (medium to high category). The total nitrogen content in the grid ranged from 0.20 to 0.25 (low to medium category), while in the plate it ranged from 0.21 to 0.29 (medium category). The C/N ratio in the grid ranged from 11.16 to 17.00 (medium to high category), and in the plate from 10.44 to 14.75 (low to medium category). The key findings of this research include the identification of organic carbon and nitrogen content in the soil, which enables recommendations for the application of organic and nitrogen fertilizers in the study area.